Anak ku Sazali - P. Ramlee, Tan Sri, 1929-1973
The movie tells us the story of Hassan who has great passion for music. Hassan and Ani eloped and ran away to Singapore knowing that their marriage will never be approved by Ani's parents. Hassan soon made a name for himself as a musician and later as a composer. His compositions received great reviews. Hassan was overjoyed when he found out that his wife was pregnant but it soon turned to sorrow as Ani died giving birth to a son, Sazali. Hassan turned his affection towards Sazali and soon Sazali grew up into a rich spoilt kid. Sazali grew up to become one of Singapore's most wanted men. The police was tipped off when Sazali and his gang committed burglary. Sazali was shot but managed to escape and seek shelter in his father's home. What did Hassan do?